The distribution of Birgus sp in Batu Asahan Coastal Waters, District IV Jurai Pesisir Selatan Regency, West Sumatera Province - Rio Syahputra; Rifardi Rifardi; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             This research was conducted in May 2017 in BatuAsahan Coastal Waters, District IV Jurai, Pesisir Selatan Regency, West Sumatera Province. This study aims to determine the distribution of Birgussp in BatuAsahan Beach, District IV Jurai. The method was used survey method with research location divided into three intertidal zone (upper, lower and middle) waters, consist of 3 station perpendicular to coastline where each station there is 1 transect. The distribution pattern of Birgussp in each station is clustered. Birgussp species found in 3 species of Birguscavipes, BirgusregosusandBirgusbrevamanus the most dominant type of Birguscavipes found in almost every station found. The population abundance of Birgussp is the most common in station III with the amount of 18.67 ind / m². The dominance index at each research station ranged from 0.4266 - 0.6504, The dominance index that has been obtained shows no more dominant type. Keywords: Birgus sp, clustered, Intertidal zone